Validitas Bahan Ajar Statistika Terapan Berbasis ICT Terintegrasi Proyek - Hamidah Suryani Lukman; Ana Setiani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
This paper describes the validity analysis of applied statistical teaching materials based on ICT and project integrated which one of the first step of research and development, namely expert judgment. The instruments used in this study are the validation sheet of materials and ICT experts. The material expert validation sheet comprises 44 statements covering 4 aspects of the assessment, namely the feasibility of the material aspect, the feasibility of the language aspect, the feasibility of the teaching materials presentation aspect, and the feasibility of teaching effects on the student learning process. The ICT expert validation sheet consists of 15 statements regarding the assessment of the feasibility of teaching materials in terms of ICT aspects. Validator involved in this research is 3 experts. Data of this research are analyzed descriptively. The result of research indicate that 86,60% criteria of material aspect have been fulfilled and categorized as very good (4,33), 86% criteria of language aspect have been fulfilled and categorized as very good (4,30), 90% has been fulfilled and categorized as excellent (4.50), 96.60% criteria of the effects of the teaching materials on the learning process of students have been fulfilled and categorized as excellent (4.83), and 94.60% criteria of ICT aspects have been met and categorized as excellent (4.73). Based on these data, 91.60% of the criteria for the assessment of the feasibility of applied statistical teaching materials based on ICT and project integrated developed have been fulfilled, classified as excellent category (4.58) and appropriate for use in learning.